2009
DOI: 10.1002/jnr.22328
|View full text |Cite
|
Sign up to set email alerts
|

Taurine stimulates proliferation of mice embryonic cultured neural progenitor cells

Abstract: Taurine is present in high levels in fetal brain which decrease in the adult, suggesting its role in brain development. In some regions of taurine deficient animals cells show defective migration and the presence of numerous mitotic figures, suggesting a delay in cell proliferation. To know more about the role of taurine in the developing brain cells, the present study investigated whether taurine is a factor involved in proliferation or/and viability of neural progenitor cells (NPC). NPC were obtained from 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
(37 reference statements)
5
29
0
Order By: Relevance
“…This result confirms our previous observation in cells obtained from the mesencephalon of embryonic mouse brain, as well as the recently reported results on NPCs from hippocampi of rodent embryos [11,12]; however, this is the first study on taurineʼs effects in NPCs of human origin. A study by Chen et al [17] reported that taurine (8-10 m M ) increased the proliferation of human fetal neuronal cells, although these are not NPCs but cells committed to form neurons.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This result confirms our previous observation in cells obtained from the mesencephalon of embryonic mouse brain, as well as the recently reported results on NPCs from hippocampi of rodent embryos [11,12]; however, this is the first study on taurineʼs effects in NPCs of human origin. A study by Chen et al [17] reported that taurine (8-10 m M ) increased the proliferation of human fetal neuronal cells, although these are not NPCs but cells committed to form neurons.…”
Section: Discussionsupporting
confidence: 81%
“…A study by Chen et al [17] reported that taurine (8-10 m M ) increased the proliferation of human fetal neuronal cells, although these are not NPCs but cells committed to form neurons. The taurine-induced proliferation of NPCs is significant in cells of embryonic origin, at 28% in hippocampal cells and 39% in the mesencephalon [11,12]. This effect of taurine is even more evident in cells obtained from the SVZ of the adult mouse, showing that taurine increased the number of NPCs in the culture by 120%, one of the highest reported percentages for any of the molecules that positively regulate NPC proliferation [13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Its cytoprotective role has been reported in various cell types, including hepatocytes, vascular smooth muscle cells, and PC12 rat pheochromocytoma cells (Kearns and Dawson 2000;Li et al 2004;Heidari et al 2012). It could also stimulate cell proliferation in neural stem/progenitor cells, neural progenitor cells and osteoblast cells (Jeon et al 2007;Hernandez-Benitez et al 2010. Taurine inhibited serum deprivationinduced cell apoptosis via the taurine transporter and extracellular signal-regulated kinase (ERK) signaling pathway, and increased cell proliferation by ERK 1/2 activation (Jeon et al 2007;Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1F). Given the well-established survival role of taurine in several biological processes including anti-oxidation, radioprotection, detoxification and proliferation, [27][28][29] we evaluated the role of taurine in modulating mtROS and ATP production levels. Taurine had no significant effect on both mtROS and ATP levels, indicating that TUDCA function is not dependent on its taurine-conjugated moiety (Fig.…”
Section: Tudca Prevents Differentiation-induced Mitochondrial Stressmentioning
confidence: 99%